2013
DOI: 10.1126/science.1232957
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Polytopes: Multiparticle Entanglement from Single-Particle Information

Abstract: Entangled many-body states are an essential resource for quantum computing and interferometry. Determining the type of entanglement present in a system usually requires access to an exponential number of parameters. We show that in the case of pure, multiparticle quantum states, features of the global entanglement can already be extracted from local information alone. This is achieved by associating any given class of entanglement with an entanglement polytope-a geometric object that characterizes the single-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
207
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(224 citation statements)
references
References 81 publications
4
207
0
1
Order By: Relevance
“…In [13] a characterization of multipartite entanglement in terms of even just single-party reduced states (actually, singleparty spectra) was given, but under the assumption of dealing with a pure or quasi-pure global state. In [14][15][16] the possibility of dealing with global mixed states is taken into account, and examples are given where twoqubit separable states are only compatible with global entanglement, intended in the sense of lack of total separability (see Section II for definitions).…”
Section: Introductionmentioning
confidence: 99%
“…In [13] a characterization of multipartite entanglement in terms of even just single-party reduced states (actually, singleparty spectra) was given, but under the assumption of dealing with a pure or quasi-pure global state. In [14][15][16] the possibility of dealing with global mixed states is taken into account, and examples are given where twoqubit separable states are only compatible with global entanglement, intended in the sense of lack of total separability (see Section II for definitions).…”
Section: Introductionmentioning
confidence: 99%
“…For more than three qubits there is an infinite number of SLOCC classes and the introduction of families of entanglement classes [5] has been instrumental to shed light into the increasing level of complexity [6]. Recently the concept of entanglement polytopes has provided an insightful geometrical information to discriminate the SLOCC classes [7]. Ratios of polynomial invariants can also be a very useful tool in this context [8].…”
Section: Introductionmentioning
confidence: 99%
“…In case of pure, multiparticle quantum states, the authors have shown that the features of the global entanglement can be extracted from its local information alone. Unlike the present paper, the approach in [37] is not device-independent. However, extending this idea in device-independent framework may be an interesting research direction.…”
Section: Lemma 1 (Wolf Et Al [30]): Any Two Dichotomic Quantum Measmentioning
confidence: 82%
“…In comparison to this our semi-device independent scenario assumes dimension of only one of the subsystems. Another recent work [37] by Walter et al is also quite worthy to mention here. They have introduced a geometrical object, called entanglement polytope which characterizes the eigenvalues of the single-particle states in any given class of entanglement.…”
Section: Lemma 1 (Wolf Et Al [30]): Any Two Dichotomic Quantum Measmentioning
confidence: 99%